2012
DOI: 10.1155/2012/147202
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Antidiabetic Principle from Fruit Rinds ofPunica granatum

Abstract: Present study was aimed to isolate and evaluate the antidiabetic activity of phytoconstituents from fruit rinds of Punica granatum. With the above objectives Valoneic acid dilactone (VAD) was isolated from methanolic fruit rind extracts of Punica granatum (MEPG) and confirmed by 1H-NMR, 13C-NMR, and mass spectral data. Antidiabetic activity was evaluated by Aldose reductase, α-amylase and PTP1B inhibition assays in in vitro and Alloxan-induced diabetes in rats was used as an in vivo model. In bioactivity studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 32 publications
1
23
0
1
Order By: Relevance
“…The fruit was used as a 'blood purifier' and to cure parasitic infections, aphthae (mouth ulcers) and diarrhoea. Isolation of antidiabetic principles from the fruit rinds of P. granatum was also reported (Jain et al 2012). Its flowering part has been recommended in Unani literature as a remedy for diabetes (Ali & Sharma 2006).…”
Section: Please Scroll Down For Articlementioning
confidence: 90%
“…The fruit was used as a 'blood purifier' and to cure parasitic infections, aphthae (mouth ulcers) and diarrhoea. Isolation of antidiabetic principles from the fruit rinds of P. granatum was also reported (Jain et al 2012). Its flowering part has been recommended in Unani literature as a remedy for diabetes (Ali & Sharma 2006).…”
Section: Please Scroll Down For Articlementioning
confidence: 90%
“…A recent study by Jain et al [32] has shown the probable mechanism of action of PP. They have isolated and purified a compound Valoneic acid dilactone (VAD) from the methanolic extract of Punica granatum (MEPG).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…Interestingly, many plant derived constituents such as aconitine, berberine, piperine, baicalin, vitexin, rutin, apigenin, chrysin, eugenol, ellagic acid, gallic acid, quercetin, kaemferol, abietic acid, and α-terpineol are well proved to possess anticonvulsant activity in various experimental models [ 39 ]. In these lines, some of the these phytocompounds such as gallic acid, ellagic acid, rutin, corilagin, kaempferol, luteolin, myricetin, quercetin, and quercimetrine were previously isolated from P. granatum [ 40 ]; based on these observations, we can conclude that the MLPG is eliciting its anticonvulsant activity by synergestic interaction of some these compounds, through enhanced GABA levels in the brain.…”
Section: Discussionmentioning
confidence: 82%